Effects of ionic liquid on the hydroxylpropylmethyl cellulose (HPMC) solid polymer electrolyte - Chong, M.Y.; Liew, C.W.; Numan, A.; Yugal, K.; Ramesh, K.; Ng, H.M.; Chong, T.V.; Ramesh, S. (Springer Verlag, 2016)
Biodegradable solid polymer electrolyte (SPE) is prepared by solution-casting technique using low-cost cellulose derivative, hydroxypropylmethyl cellulose (HPMC) as a host polymer. Owing to the hydrophobic nature of this polymer, it is predicted to exhibit low ionic conductivity upon addition of magnesium trifluoromethanesulfonate (MgTf2) salt. Therefore, ionic liquid (IL), 1-butyl-3-methylimidazolium trifluoromethanesulfonate (BMIMTf), is added in order to enhance its ionic conductivity. Based on the findings, the ionic conductivity at room temperature and the dielectric behaviors of the SPE complex improved upon incorporation of 40 wt.% IL. On top of that, addition of IL reduces the degree of crystallinity and the glass transition temperature (Tg) of the SPE. The conductivity-temperature plot revealed that the transportation of ions in these films obey Arrhenius theory. The interaction between SPE complex, MgTf2 salt, and BMIMTf is investigated by means of Fourier transform infrared (FTIR) spectroscopy through the change in peak intensity around 3413, 1570, and 1060 cm−1, which are responsible for –OH stretching band, C–C and C–N bending modes of cyclic BMIM+, and C–O–C stretching band, respectively.